2017
DOI: 10.22159/ijpps.2017v9i4.15708
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms as Chemical Factories for Isolation of Meta-Bolomes From Mesophilic Soil

Abstract: Objective: To investigate the micro-flora of the mesophilic soil of Rajasthan for isolation of novel compounds having antibacterial potentials. Methods:In present experiments, bacterial colonies were isolated from four different regions of Jaipur, Rajasthan and screened for antimicrobial efficacy against five selected pathogens Pseudomonas aeruginosa MTCC 7093, Staphylococcus aureus MTCC 7443, Escherichia coli MTCC 40, Klebsiella pneumoniae MTCC 530, and Bacillus subtillis MTCC 121. Antimicrobial efficacy agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…It has observed that while increasing the concentration of polymers (Chitosan) in the formulation (NS4, 5%), the swelling property of nanospheres is also increased as suggested by Sharma R et al, (2012). The swelling aspects of nanospheres reflecting a gel like structure around the nanospheres, controlled the drug release of drug [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has observed that while increasing the concentration of polymers (Chitosan) in the formulation (NS4, 5%), the swelling property of nanospheres is also increased as suggested by Sharma R et al, (2012). The swelling aspects of nanospheres reflecting a gel like structure around the nanospheres, controlled the drug release of drug [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, an optimization model for microbial mediated degradation of oil [4], diesel [5], endosulfan [6], and textile dye [7] has been reported. Today, at global level healthcare is facing the problem of the emergence of multi-resistant bacteria thus the threat of epidemics and pandemics [8] and became a major global health problem [9,10]. Hence, the present study was designed to isolate native DWW degrading microbes under optimized conditions and treatment of DWW under aerobic and anaerobic conditions and determination of antimicrobial resistance profile of efficient strains by disc diffusion method.…”
Section: Introductionmentioning
confidence: 99%